PELATIHAN PENGGUNAAN BUKU TEKS BERMUATAN HOTS PADA MATERI MULTIKULTUR BAGI GURU SEJARAH SMA KOTA JAYAPURA - Handoko, Susanto T.; Hasirun, La Ode; Kulyasin; Loppies, Megiridha (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Negeri Jakarta, 2023)
Abstract This training is motivated by the demands of 21st Century Learning, namely learning that is innovative, creative and fun for students by carrying the spirit of independent learning. Understanding and awareness of Indonesianness must be known by all Indonesians, especially history teachers and students. This awareness is important because Indonesia is a pluralistic country consisting of various ethnic groups, regional languages, religions, and belief groups. This training aims to equip history teachers in the use and internalization of HOTS content history text books on multicultural material. The training methods are in the form of: lectures, questions and answers, discussions, making teaching modules, and teaching practice. The results of the training show that history teachers in implementing the independent curriculum are able to develop innovations in learning history that integrate high-order thinking skills in multicultural material at the senior high school level. Multicultural material in history textbooks can be implemented on the concepts of: culture, multicultural values, social and cultural conflict, race, ethnicity, religion and beliefs, and national identity. Abstrak Pelatihan ini dilatarbelakangi oleh adanya tuntutan Pembelajaran Abad Ke-21 yaitu pembelajaran yang inovatif, kreatif dan menyenangkan bagi peserta didik dengan mengusung semangat merdeka belajar. Pemahaman dan kesadaran mengenai Keindonesiaan wajib diketahui oleh segenap bangsa Indonesia, terutama guru mata pelajaran sejarah dan peserta didik. Kesadaran ini penting karena Indonesia adalah negara majemuk yang terdiri dari beragam suku bangsa, bahasa daerah, agama, dan kelompok penghayat kepercayaan. Pelatihan ini bertujuan untuk membekali guru sejarah dalam penggunaan dan internalisasi buku teks mata pelajaran sejarah bermuatan HOTS pada materi multikultur. Metode pelatihan berupa: ceramah, tanya jawab, diskusi, pembuatan modul ajar, dan praktik mengajar. Hasil pelatihan menunjukkan bahwa guru sejarah dalam implementasi kurikulum merdeka mampu mengembangkan inovasi pembelajaran sejarah yang mengintegrasikan keterampilan berpikir tingkat tinggi pada materi multikultur di jenjang sekolah menengah atas. Materi multikultur dalam buku teks mata pelajaran sejarah dapat diimplementasikan pada konsep: kultural, nilai-nilai multikultural, konflik sosial dan budaya, ras, etnis, agama dan kepercayaan, dan identitas nasional.